Exploring the potential of shrimp paste (Belacan) and its indigenous microorganisms (IMO) as a growth enhancer for Capsicum annum L. (chilli) plants - Abedelazeez, Khudair J.D.; Ahmad Fauzi, Nur Aisyah Syahirah; Zainuddin, Nurazlin; Mohd Zaini, Nurul Solehah; Yaacob, Jamilah Syafawati; Abd Rahim, Muhamad Hafiz (Malaysian Society of Applied Biology, 2025)
In recent years, there has been growing interest in utilizing Indigenous Microorganisms (IMO) as plant growth-promoting agents, with studies demonstrating their effectiveness in enhancing crop growth. Despite local practices utilizing food-based substrates, limited reports exist on the application of IMO from fermented foods to enhance the growth of Capsicum annum L. (chili) plants. Therefore, this study aimed to investigate the mechanism of Belacan (fermented shrimp paste) as a biofertilizer in promoting the growth of Capsicum annum L. Belacan was supplemented with molasses as a carbon source, and the cultured bacteria were subsequently isolated and identified using nucleotide analysis of the 16S rRNA region. Two major bacterial isolates, Bacillus velezensis, and Lysinibacillus fusiformis, were identified as potential plant-growth-promoting bacteria, with nutrient solubilization and auxin production capability. The application of belacan on chili plants revealed that they significantly enhanced plant growth parameters, including shoot length, leaf length, width, thickness, and chlorophyll content, compared to the control group. These findings suggest that IMO from Malaysian fermented foods hold potential as biofertilizers to promote the growth of chili plants, contributing to the advancement of environmentally friendly and nutritionally rich agriculture.